2020
DOI: 10.1002/med.21757
|View full text |Cite
|
Sign up to set email alerts
|

Propolis: A useful agent on psychiatric and neurological disorders? A focus on CAPE and pinocembrin components

Abstract: Propolis consists of a honeybee product, with a complex mix of substances that have been widely used in traditional medicine. Among several compounds present in propolis, caffeic acid phenethyl ester (CAPE), and pinocembrin emerge as two principal bioactive compounds, with benefits in a variety of body systems. In addition to its well‐explored pharmacological properties, neuropharmacological activities have been poorly discussed. In an unprecedented way, the present review addresses the current finding on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 76 publications
(124 reference statements)
0
16
0
Order By: Relevance
“…Propolis, a honeybee product, is a resinous product obtained from different plant parts mixed with beeswax and bee salivary enzymes and represents a multimillion dollar market [1,2]. It has been used in traditional medicine for many years due to its anti-microbial, anti-inflammatory, anti-oxidant, immunomodulator, anti-mutagenic, and carcinostatic effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Propolis, a honeybee product, is a resinous product obtained from different plant parts mixed with beeswax and bee salivary enzymes and represents a multimillion dollar market [1,2]. It has been used in traditional medicine for many years due to its anti-microbial, anti-inflammatory, anti-oxidant, immunomodulator, anti-mutagenic, and carcinostatic effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Its color varies from yellowish green to dark brown, and odor from odorless to aromatic, and depends on its botanical source, origin of place, and bee characteristics such as strain and age [ 1 ]. Besides the structural and functional attributes of propolis for bees [ 2 ], it has been reported to possess a variety of therapeutic potentials for human use [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ] since ancient times. There are mainly two kinds of propolis known that differ in their constituents: New Zealand propolis possesses CAPE (Caffeic Acid Phenethyl Ester) and Brazilian green propolis that possesses Artepillin C (3,5-diprenyl-4-hydroxycinnamic acid, ARC) as pre-dominant bioactive compounds [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Takeda et al showed that caffeic acid possesses antidepressive properties in a mice model of depression, reducing the duration of immobility in the forced swimming test. They also demonstrated that caffeic acid reversed the depression-related reduced BDNF (da Silveira et al, 2021;Takeda et al, 2006). Mehrotra et al reported the protective effects of caffeic acid against inflammatory pain by averting the production of myeloperoxidase, malondialdehyde nitrite, and a drop in neutrophil infiltration in the inflamed tissue (Mehrotra, Shanbhag, Chamallamudi, Singh, & Mudgal, 2011).…”
Section: Discussionmentioning
confidence: 96%